KANSHA TO WABI - Elizabeth Ika Hesti Hesti Aprilia Nindia Rini (IZUMI, 2014)
Abstract  Greetings seems not important, but it is necessary in human relationship. Not to know how to use greetings can lead us to misunderstandings that would be bad for the relationship that has existed. Kansha (gratitude) and wabi (apology) is one of them. Kansha and wabi expressed using standard existing idiomatic expressions, describing the facts that occurred, describing the feeling of the speaker, an expression that is not a word. Keywords : greetings, kansha, wabi